Spontaneous Pneumomediastinum and Subcutaneous Emphysema following Cocaine Inhalation and Ecstasy Ingestion - Samantha Jaensch; Sang Hwang; Tony Shih-Wei Kuo (Case Reports in Otolaryngology)
Spontaneous pneumomediastinum (SPM) and subcutaneous emphysema are rare complications of illicit drug abuse. Thorough history, examination, and investigations are required to rule out fatal complications such as oesophageal perforation. We present a case of a 21-year-old male presenting with pleuritic chest pain one day after cocaine inhalation and ingesting ecstasy. Conservative supportive management is appropriate when this occurs spontaneously without radiological evidence of visceral perforation.